PENGARUH MODEL PEMBELAJARAN RESOLUSI KONFLIK BERBASIS MASALAH KONTEKSTUAL TERHADAP HASIL BELAJAR PKn SISWA SD INPRES MALLENGKERI 2 KOTA MAKASSAR - Irma Susiyanti; Rosleny B.; Muhajir . (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
THE INFLUENCE OF CONTEXTUAL PROBLEM-BASED CONFLICT RESOLUTION LEARNING MODELS ON LEARNING OUTCOMES OF CITIZENSHIP EDUCATION OF INPRES MALLENGKERI 2 ELEMENTARY SCHOOL STUDENTS IN MAKASSAR CITYThis study aims to determine the effect of the contextual problem-based conflict resolution learning model on student Civics learning outcomes at SD Inpres Mallengkeri 2, Makassar City. This study is a quasi-experimental study using a non-equivalent control group design. Subjets in this study amounted to 48 students with a population off all class IV students of cluster 3, Tamalate District, Makassar city. The sampling technique was carried out by purposive sampling, the sample used was class IV.A as the experimental class and class IV.B as the control class. Data collection techniques in this study werw carried out using test techniques quantitative data processing was carried out using SPSS for windows software. The results of the research based on descriftive analysis show that (1) the avarege civics learning outcome in the experimental class is 87.71 and the control class is 77.50 which means that there is an increase in student civics learning outcomes after following contextual problem-based complicit resolution learning models at SD Inpres Mallengkeri 2 Makassar City, (2) The result of imferential analysis show that there is an influence of the contextual problem-based conflict resolution learning model on student civics learning outcomes at SD Inpres Malllengkeri 2, Makassar City. This is based on the t test table (independent sample t-test), the sig value is obtained 0.000 0.005.